The Cilect Prize 2011 - Disc 4 - Gendreau, Thomas; Speckenbach, Jan; Moutaharik, Bouchra; Witzø, Hallvar; Spinell, Natalie
Spatzen (2009): A man meets a woman in a bar. They walk through the night without any reason. At dawn they separate again. A long take. [www.german-films.de]
Keywords: DVD-Video